Residue-free multi-step hole thick electrode plate and preparation method thereof, and lithium ion battery

By using ammonium bicarbonate solid particles and multiple coating, drying and rolling operations in the lithium-ion battery electrode sheet, a residual gradient difference porous structure is formed, and the conductivity difference and sodium ions of the electrode sheet in the prior art are solved. The residual problem achieves a lithium-ion battery with high energy density and long cycle performance.

CN119495714APending Publication Date: 2025-02-21MEIZHOU LIANGNENG NEW ENERGY SCI & TECHCO

Patent Information

Application Number
CN202411618042.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When the existing lithium-ion battery electrode sheet increases thickness to increase energy density, the transmission distance of lithium ions becomes longer, resulting in poor conductivity and difficult electrolyte to infiltrate. The sodium bicarbonate used at the same time will cause sodium ions to remain. Increase internal resistance.

Method used

Using ammonium bicarbonate solid particles, through multiple coating operations, drying and rolling operations, a residual gradient porous structure is formed, ensuring that the conductivity and electrolyte emollience of the electrode sheet are improved, while avoiding ammonium bicarbonate solids. Residue of particles.

Benefits of technology

A thick electrode sheet without residual multi-step holes is realized, which improves the wetting and conductivity of the electrolyte, reduces internal resistance, extends the circulation performance of the lithium-ion battery, and saves drying energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495714A_ABST
    Figure CN119495714A_ABST
Patent Text Reader

Abstract

The invention provides a thick electrode plate without residual multi-step holes, a preparation method of the thick electrode plate and a lithium ion battery. According to the preparation method, the current collector is obtained; sequentially carrying out n times of coating operation on the slurry; the slurry for the first coating operation does not contain ammonium bicarbonate solid particles; slurry from the second coating operation to the nth coating operation contains ammonium bicarbonate solid particles, and the use amount of the ammonium bicarbonate solid particles used in each coating operation is increased along with the increase of the coating operation times; and sequentially carrying out drying operation and rolling operation on the slurry after each coating operation, so that the ammonium bicarbonate solid particles are gasified during drying, and the obtained non-residue multi-stepped-hole thick electrode plate forms a down-gradient-difference porous structure. According to the preparation method, the characteristic that the ammonium bicarbonate solid particles are easy to decompose at low temperature and free of residues is utilized, on the premise that it is guaranteed that the porous structure along the gradient difference is prepared, the phenomenon that the coating is prone to cracking in the drying process is avoided, and drying energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium ion batteries, and in particular to a thick electrode sheet without residual multi-step holes, a preparation method thereof, and a lithium ion battery. Background Art

[0002] At present, with the increasing demand for portable electronic products and electric vehicles, people are constantly pursuing longer service life of electronic products. Therefore, the batteries configured in electronic products must have higher energy density.

[0003] Existing batteries, such as lithium-ion batteries or sodium-ion batteries, generally increase the energy density of the battery by increasing the thickness of the electrode sheet. However, the increase in the thickness of the electrode sheet will cause the transmission distance of lithium ions or sodium ions to become longer, which will cause the problem of poor conductivity and difficulty in electrolyte infiltration.

[0004] In order to solve the above problems, Chinese patent document No. CN 114914392 A discloses a method for preparing a porous electrode of a sodium ion battery, wherein sodium bicarbonate is added to the slurry of the first coating, and sodium bicarbonate is added or not added to the slurry of the second and multiple coatings to form pores in the coating, so as to effectively solve the problems of poor conductivity and difficult electrolyte infiltration in thick coatings.

[0005] Although the above-mentioned electrode sheet solves the problem of difficult electrolyte infiltration and poor conductivity, when the above-mentioned sodium bicarbonate is used in a lithium-ion battery, it will cause the problem of residual sodium ions, and the residual sodium ions will cause the internal resistance of the lithium-ion battery to increase, thereby affecting the cycle performance of the lithium-ion battery.

[0006] For another example, Chinese patent document No. CN 115548273 A discloses a method for preparing an electrode sheet, wherein a mixture of a silicon-containing electrode material and a pore-forming filler is formed into an outer electrode film, and a carbon-containing electrode material is formed into an inner electrode film; the outer electrode film and the inner electrode film are roll-compounded to obtain a composite laminate, so that the outer electrode film and the inner electrode film can form a porous electrode film. Although the electrolyte infiltration problem is improved, when the outer electrode film and the inner electrode film are roll-compounded, the particles of the active material are easily broken and pulverized due to uneven or excessive rolling pressure during the rolling process, thereby increasing the internal resistance of the battery.

[0007] Furthermore, since the above-mentioned electrode sheets use high-temperature gasification materials such as iodine or aluminum chloride, which have a high gasification temperature, in order to avoid the problem of residual iodine or aluminum chloride, a higher temperature is usually used for a longer drying time. Long-term high-temperature drying may cause cracking of the electrode sheets, thereby affecting the battery fluid retention problem. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a thick electrode sheet with multi-step pores without residue and a preparation method thereof, and a lithium-ion battery, which utilizes the low-temperature, easy-to-decompose and residue-free properties of ammonium bicarbonate solid particles, ensures that a residual-free gradient porous structure is prepared, and also ensures that the coating is not prone to cracking and other undesirable phenomena during the drying process, and saves energy consumption for drying.

[0009] The purpose of this disclosure is achieved through the following technical solutions:

[0010] A method for preparing a thick electrode sheet without residual multi-step holes, comprising:

[0011] Obtaining a current collector; performing n coating operations on the slurry in sequence, where n≥3 and n is a positive integer; characterized in that,

[0012] The slurry of the first coating operation does not contain solid ammonium bicarbonate particles; the slurries of the second coating operation to the nth coating operation all contain the solid ammonium bicarbonate particles, and the amount of the solid ammonium bicarbonate particles used in each coating operation increases with the increase in the number of coating operations;

[0013] The preparation method further comprises:

[0014] The slurry is dried and rolled in sequence after each coating operation, so that the ammonium bicarbonate solid particles are gasified during drying, so that the obtained thick electrode sheet without residual multi-step pores can form a gradient-differential porous structure, and the porosity of the gradient-differential porous structure gradually increases from one end close to the current collector to the end away from the current collector.

[0015] In one embodiment, the weight percentage of the ammonium bicarbonate solid particles used in each coating operation is: y = (0.1-0.4) * (n-1), wherein n is the number of coating operations.

[0016] In one embodiment, the temperature of the drying operation is 60° C. to 100° C., and the time of the drying operation is 5 min to 30 min.

[0017] In one of the embodiments, the rolling rate during the rolling operation is 80% to 90%.

[0018] In one of the embodiments, the solid content of the slurry is 40% to 75%, and the viscosity of the slurry is 5000 mPa.s to 7000 mPa.s.

[0019] In one of the embodiments, the slurry is a positive electrode slurry, and the active material of the positive electrode slurry includes the following weight percentages: 96.0% to 99.0% positive electrode material, 0.5% to 1.5% conductive agent, and 0.5% to 2.0% binder.

[0020] In one embodiment, the positive electrode material includes LiCoO2, LiMn2O4, LiFePO4 and Li(Ni x Co y Mn z ) at least one of O2.

[0021] In one embodiment, the coating thickness of the coating operation is 25um to 50um; and / or,

[0022] Each coating operation of the n coating operations is a double-sided coating operation.

[0023] A thick electrode sheet without residual multi-step holes is prepared by using the method for preparing a thick electrode sheet without residual multi-step holes described in any of the above embodiments.

[0024] A lithium-ion battery comprises a thick electrode sheet without residual multi-step holes as described in any of the above embodiments.

[0025] Compared with the prior art, the present invention has at least the following advantages:

[0026] 1) Since the added ammonium bicarbonate solid particles will decompose to form ammonia, water vapor and carbon dioxide gas when heated during drying, the decomposition gas helps to form a porous structure, and the generated ammonia, water vapor and carbon dioxide gas will be pumped away, effectively avoiding the problem of residual impurities in the thick electrode sheet without residual multi-step pores, ensuring that the added ammonium bicarbonate solid particles will not have residual impurities, thereby effectively avoiding the problem of traditional residual impurities affecting the internal resistance of lithium-ion batteries.

[0027] 2) Since the decomposition temperature of ammonium bicarbonate solid particles is between 30°C and 60°C, the drying temperature of the present invention is significantly lower than that of traditional iodine, aluminum chloride, and sodium bicarbonate. Thus, there is no need to adjust the traditional drying operating conditions to reduce the workload of adjustment. The lower drying temperature can effectively avoid the undesirable phenomenon of surface cracking of the thick electrode sheet without residual multi-step holes due to the high drying temperature, thereby ensuring that the surface of the thick electrode sheet without residual multi-step holes is smooth and flat without cracks. At the same time, the lower drying temperature also saves energy consumption for drying, effectively reducing the cost of the drying process.

[0028] 3) Since the slurry of the first coating operation does not contain ammonium bicarbonate solid particles; the slurries of the second coating operation to the nth coating operation all contain ammonium bicarbonate solid particles, and the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations; at the same time, the slurry after each coating operation is dried and rolled in sequence, so that the thick electrode sheet without residual multi-step pores finally prepared can form a gradient-differential porous structure, that is, the porosity of the coating close to the current collector is smaller than the porosity of the coating far from the current collector, so that the gradient-differential porous structure is conducive to the rapid penetration of the electrolyte, so as to accelerate the movement of lithium ions in the thick electrode sheet without residual multi-step pores, and effectively avoid the problem of increased internal resistance due to the electrolyte not penetrating the thick electrode sheet without residual multi-step pores, and the gradient-differential porous structure helps to increase the electrolyte retention, thereby improving the cycle retention rate of the lithium-ion battery.

[0029] 4) Since the slurry is dried and rolled in sequence after each coating operation, each coating operation needs to be dried and rolled first, that is, the drying operation can form and fix the slurry on the current collector to obtain a coating, and the drying operation can also effectively remove the ammonium bicarbonate solid particles to ensure that the dried coating has a corresponding porosity; the rolling operation can improve the adhesion between the active material, the conductive agent and the adhesive in the coating and the current collector, and effectively reduce the bulging of the pores caused by the gasification of the ammonium bicarbonate solid particles. The problem of increased internal resistance of lithium-ion batteries is solved, and the rolling operation also improves the smoothness and flatness of the coating surface of the thick electrode sheet without residual multi-step holes. In this way, multiple batch drying and multiple batch rolling operations are achieved for the thick electrode sheet without residual multi-step holes to ensure that the prepared thick electrode sheet without residual multi-step holes has a smooth gradient porous structure, small internal resistance, high liquid retention and is smooth and flat without cracks, effectively avoiding the problem of large internal resistance caused by uneven or excessive rolling pressure in traditional one-time rolling, which causes the particles of active material to break and pulverize. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 The present invention is a flowchart of a method for preparing a thick electrode sheet without residual multi-step holes according to an embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present disclosure, the present disclosure will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present disclosure are given in the drawings. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present disclosure more thoroughly and comprehensively understood.

[0033] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present disclosure. The terms used herein in the specification of the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] The present disclosure provides a method for preparing a thick electrode sheet without residual multi-step holes. The method comprises the following steps: obtaining a current collector; sequentially performing n coating operations on the slurry, wherein n≥3, and n is a positive integer; wherein the slurry of the first coating operation does not contain solid ammonium bicarbonate particles; the slurries of the second coating operation to the nth coating operation all contain solid ammonium bicarbonate particles, and the amount of solid ammonium bicarbonate particles used in each coating operation increases with the increase in the number of coating operations; sequentially performing drying operations and rolling operations on the slurry after each coating operation, so that the solid ammonium bicarbonate particles are gasified during drying, so that the obtained thick electrode sheet without residual multi-step holes can form a gradient-differential porous structure, and the porosity of the gradient-differential porous structure gradually increases from one end close to the current collector to one end away from the current collector.

[0036] The above-mentioned method for preparing a thick electrode sheet with no residual multi-step holes, because the added ammonium bicarbonate solid particles will decompose to form ammonia, water vapor and carbon dioxide gas when heated during drying without residual impurities, so that the decomposed ammonium bicarbonate solid particles contribute to the porous structure, effectively avoiding the problem of residual impurities in the traditional thick electrode sheet without residual multi-step holes; and because the decomposition temperature of the ammonium bicarbonate solid particles is relatively low, there is no need to adjust the traditional drying operating conditions to reduce the workload of adjustment, and the lower drying temperature can effectively avoid the undesirable phenomenon of surface cracking of the thick electrode sheet without residual multi-step holes due to the high drying temperature, so as to ensure that the surface of the prepared thick electrode sheet without residual multi-step holes is smooth and flat without cracks, and at the same time, the lower drying temperature also saves the energy consumption of drying, effectively reducing the drying process The processing cost is reduced; since the slurry of the first coating operation does not contain ammonium bicarbonate solid particles; the slurries of the second coating operation to the nth coating operation all contain the ammonium bicarbonate solid particles, and the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations; at the same time, in conjunction with the drying and rolling operations, the gradient gradient porous structure of the thick electrode sheet without residual multi-step holes is finally prepared, so that the gradient gradient porous structure is conducive to the rapid penetration of the electrolyte, so as to accelerate the movement of lithium ions in the thick electrode sheet without residual multi-step holes, and effectively avoid the problem of increased internal resistance due to the electrolyte not penetrating the thick electrode sheet without residual multi-step holes, and the gradient gradient porous structure helps to increase the electrolyte retention, thereby improving the cycle retention rate of the lithium-ion battery. Since the slurry is dried and rolled in turn after each coating operation, multiple batch drying and multiple batch rolling operations are achieved for the thick electrode sheet without residual multi-step holes, so as to ensure that the prepared thick electrode sheet without residual multi-step holes has a smooth gradient porous structure, small internal resistance, high liquid retention and is smooth and flat without cracks, effectively avoiding the problem of large internal resistance caused by uneven or excessive rolling pressure in traditional single rolling, which causes the particles of active material to break and pulverize.

[0037] See also Figure 1 In order to better understand the technical solution and beneficial effects of the present disclosure, the present disclosure is further described in detail below in conjunction with specific embodiments. A method for preparing a thick electrode sheet without residual multi-step holes in one embodiment includes some or all of the following steps:

[0038] S101, obtaining a current collector. It is understood that the current collector can provide good support for the slurry, so that multiple coating operations can be performed on the current collector in the future, thereby obtaining a multi-layer coating on the current collector.

[0039] In one embodiment, the current collector is a thick aluminum foil. It can be understood that if the thickness of the aluminum foil is lower than 8um, it is impossible to provide good tensile strength for subsequent multiple rolling, that is, the problem of aluminum foil breaking is easy to occur in the subsequent process. If the aluminum foil is thicker than 13um, the thick aluminum foil accounts for a large proportion under the same unit volume, resulting in a decrease in the thickness and number of active slurry coating, which is not conducive to the development of thin and high-energy thick electrode sheets. Therefore, in the present disclosure, by controlling the thick aluminum foil to be 8um to 13um, while ensuring that the thick aluminum foil can provide good tensile strength for subsequent multiple rolling, it also maximizes the proportion of active slurry coating under the same unit volume, which is conducive to the development of thin and high-energy thick electrode sheets. Specifically, in a preferred embodiment, the thickness of the thick aluminum foil is 13um. Since the thick aluminum foil with a thickness of 13um has higher tensile strength, higher elongation and stable processing performance, it can better ensure that the problem of aluminum foil breaking will not occur during the subsequent multiple rolling processes.

[0040] S102, performing n coating operations on the slurry in sequence, n≥3, and n is a positive integer; wherein the slurry of the first coating operation does not contain ammonium bicarbonate solid particles; the slurries of the second coating operation to the nth coating operation all contain the ammonium bicarbonate solid particles, and the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations.

[0041] It can be understood that since the slurry of the first coating operation does not contain ammonium bicarbonate solid particles; the slurries of the second coating operation to the nth coating operation all contain the ammonium bicarbonate solid particles, and the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations; at the same time, in conjunction with the drying and rolling operations, the gradient differential porous structure of the thick electrode sheet without residual multi-step pores is finally prepared, that is, the porosity of the coating close to the current collector is smaller than the porosity of the coating far from the current collector. In this way, the gradient differential porous structure is conducive to the rapid penetration of the electrolyte, so as to accelerate the movement of lithium ions in the thick electrode sheet without residual multi-step pores, and effectively avoid the problem of increased internal resistance due to the electrolyte not penetrating the thick electrode sheet without residual multi-step pores, and the gradient differential porous structure helps to increase the electrolyte retention amount, thereby improving the cycle retention rate of the lithium-ion battery.

[0042] S103. After each coating operation, the slurry is dried and rolled in sequence to vaporize the ammonium bicarbonate solid particles during drying, so that the obtained thick electrode sheet without residual multi-step pores can form a gradient-differential porous structure, and the porosity of the gradient-differential porous structure increases gradually from one end close to the current collector to the end away from the current collector.

[0043] It can be understood that, since the slurry is subjected to a drying operation and a rolling operation in sequence after each coating operation, the coated slurry is first subjected to a drying operation, and the drying operation, on the one hand, enables the slurry to be formed and fixed on the current collector to obtain a coating, and on the other hand, the drying operation can effectively remove the ammonium bicarbonate solid particles to ensure that the dried coating has a corresponding porosity; then, the dried coating is subjected to a rolling operation, and bubbles are generated by the thermal decomposition of the ammonium bicarbonate solid particles during the drying process, and the bubbles can gather in the slurry and form relatively dense bubbles, and the denser bubbles can discharge the liquid in the slurry and form channels perpendicular to the surface of the slurry, that is, form pores, but the decomposition products of the ammonium bicarbonate solid particles are 3 Different gases are introduced into the coating, which may easily cause bulging around the pores of the ammonium bicarbonate solid particles during drying, resulting in a larger surface roughness of the dried coating and an increase in the internal resistance of the lithium-ion battery. The coating after the drying operation is rolled, and the rolling operation can better flatten the bulges around the pores to improve the smoothness and flatness of the coating surface. The rolling operation can also effectively reduce the gaps between the active materials, conductive agents and adhesives around the pores, thereby improving the conductivity of the thick electrode sheet without residual multi-step holes, thereby reducing the internal resistance of the thick electrode sheet without residual multi-step holes, and effectively avoiding the problem of particle breakage and pulverization of the active material caused by uneven or excessive rolling pressure in traditional one-time rolling.

[0044] It can be understood that since the slurry is dried and rolled in sequence after each coating operation, multiple batch drying and multiple batch rolling operations are achieved for the thick electrode sheet without residual multi-step holes, so as to prepare a thick electrode sheet without residual multi-step holes with a smooth gradient porous structure, small internal resistance, high liquid retention and smoothness without cracks.

[0045] The above-mentioned method for preparing a thick electrode sheet without residual multi-step pores, because the added ammonium bicarbonate solid particles will decompose to form ammonia, water vapor and carbon dioxide gas when heated during drying, the gas generated by the decomposition helps to form a porous structure, and the generated ammonia, water vapor and carbon dioxide gas will be pumped away, effectively avoiding the problem of residual impurities in the thick electrode sheet without residual multi-step pores, to ensure that the added ammonium bicarbonate solid particles will not have residual impurities, thereby effectively avoiding the problem of traditional residual impurities affecting the internal resistance of lithium-ion batteries. Further, since the decomposition temperature of the ammonium bicarbonate solid particles is between 30°C and 60°C, the drying temperature of the present disclosure is significantly lower than that of traditional iodine, aluminum chloride and sodium bicarbonate, so that there is no need to adjust the traditional drying operating conditions to reduce the workload of adjustment, and the lower drying temperature can effectively avoid the undesirable phenomenon of surface cracking of the thick electrode sheet without residual multi-step pores due to the high drying temperature, to ensure that the surface of the prepared thick electrode sheet without residual multi-step pores is smooth and flat without cracks, and the lower drying temperature also saves the energy consumption of drying, effectively reducing the cost of the drying process. Furthermore, since the slurry of the first coating operation does not contain ammonium bicarbonate solid particles; the slurries of the second coating operation to the nth coating operation all contain the ammonium bicarbonate solid particles, and the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations; at the same time, the slurry after each coating operation is dried and rolled in sequence, so that the thick electrode sheet without residual multi-step pores finally prepared can form a gradient-differential porous structure, that is, the porosity of the coating close to the current collector is smaller than the porosity of the coating far from the current collector, so that the gradient-differential porous structure is conducive to the rapid penetration of the electrolyte, so as to accelerate the movement of lithium ions in the thick electrode sheet without residual multi-step pores, and effectively avoid the problem of increased internal resistance due to the electrolyte not penetrating the thick electrode sheet without residual multi-step pores, and the gradient-differential porous structure helps to increase the electrolyte retention amount, thereby improving the cycle retention rate of the lithium-ion battery.Furthermore, since the slurry is subjected to a drying operation and a rolling operation in sequence after each coating operation, the drying operation and the rolling operation need to be performed in sequence after each coating operation, that is, the drying operation can, on the one hand, shape and fix the slurry on the current collector to obtain a coating, and on the other hand, the drying operation can also effectively remove the ammonium bicarbonate solid particles to ensure that the dried coating has a corresponding porosity; the rolling operation can improve the adhesion between the active material, the conductive agent and the adhesive in the coating and the current collector, and effectively reduce the periphery of the holes caused by the gasification of the ammonium bicarbonate solid particles. The problem of bulging causing increased internal resistance of lithium-ion batteries is solved, and the rolling operation also improves the smoothness and flatness of the coating surface of the thick electrode sheet without residual multi-step holes. In this way, multiple batch drying and multiple batch rolling operations are achieved for the thick electrode sheet without residual multi-step holes to ensure that the prepared thick electrode sheet without residual multi-step holes has a smooth gradient porous structure, small internal resistance, high liquid retention and smooth and flat surface without cracks, effectively avoiding the problem of large internal resistance caused by uneven or excessive rolling pressure in traditional one-time rolling, which causes the particles of active material to break and pulverize.

[0046] In one embodiment, the weight percentage of the ammonium bicarbonate solid particles used in each coating operation is: y = (0.1 ~ 0.4) * (n-1), wherein n is the number of coating operations, so that the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations, that is, the weight percentage of the ammonium bicarbonate solid particles used in the slurry during the third coating operation is more than the weight percentage of the ammonium bicarbonate solid particles used in the slurry during the second coating operation, and the weight percentage of the ammonium bicarbonate solid particles used in the slurry during the fourth coating operation is more than the weight percentage of the ammonium bicarbonate solid particles used in the slurry during the third coating operation, and so on, so that a multi-layer coating can be formed on the current collector after n coating operations, and the weight percentage of the ammonium bicarbonate solid particles in the coating close to the current collector gradually increases toward the weight percentage of the ammonium bicarbonate solid particles in the coating far away from the current collector, so as to ensure that the added ammonium bicarbonate solid particles can eventually form a gradient porous structure in a thick electrode sheet without residual multi-step holes.

[0047] It should be noted that in actual applications, for example, Chinese patent document No. CN1259744C discloses that ammonium bicarbonate solid can be used as a pore-forming agent. When Chinese patent document No. CN1259744C is combined with the patent document No. mentioned in the background technology, those skilled in the art will adjust the specific amount of ammonium bicarbonate solid used according to the porosity requirements to obtain a corresponding porous structure.

[0048] Although the corresponding porous structure can be obtained by the porosity requirement, the decomposition product of the ammonium bicarbonate solid particles is gas, which causes the gas production of the ammonium bicarbonate solid particles during dry gasification to cause bulging around the holes. Therefore, in the present disclosure, by controlling the weight percentage of the ammonium bicarbonate solid particles to be: y = (0.1 ~ 0.4) * (n-1), the amount of ammonium bicarbonate solid particles used in each layer is ensured to be more appropriate. In this way, on the premise that the thick electrode sheet without residual multi-step pores finally prepared has a smooth gradient porous structure, the problem of bulging around the holes caused by the gas production of the ammonium bicarbonate solid particles during dry gasification is avoided, and the thick electrode sheet without residual multi-step pores prepared is ensured to have a higher energy density.

[0049] In one embodiment, the particle size of the ammonium bicarbonate solid particles is 20um to 60um, and the particle size of the ammonium bicarbonate solid particles gradually increases from one end close to the current collector to the end away from the current collector, and the particle size difference between each adjacent ammonium bicarbonate solid particle is 5um to 20um.

[0050] It can be understood that since ammonia, water vapor and carbon dioxide gas are almost produced simultaneously when the ammonium bicarbonate solid particles are thermally decomposed, if the particle size of the ammonium bicarbonate solid particles used is relatively large, and the decomposition temperature of the ammonium bicarbonate solid particles is relatively low, there will still be a problem of bulging around the hole when drying at 60°C to 100°C; if the particle size of the ammonium bicarbonate solid particles used is too small, it will not be able to meet the pore size requirements required for production. Therefore, by controlling the particle size of the ammonium bicarbonate solid particles to be 20um to 60um, it is ensured that the particle size of the added ammonium bicarbonate solid particles is more appropriate, and the added ammonium bicarbonate solid particles are effectively avoided due to the large particle size, resulting in a large gas production during drying and gasification, which causes serious bulging around the hole, thereby ensuring that a thick electrode sheet with a smooth surface and no residual multi-step holes is prepared.

[0051] It can also be understood that although the flow rate of the electrolyte is improved to a certain extent by increasing the porosity of each coating, since the thickness of the thick electrode sheet without residual multi-step holes is relatively thick, the electrolyte still has a poor flow rate in the thickness direction of the thick electrode sheet without residual multi-step holes. Therefore, in the present disclosure, the particle size of the ammonium bicarbonate solid particles is gradually increased from the end close to the current collector to the end away from the current collector to ensure that the pore size of the coating at the end close to the current collector is smaller than the pore size of the coating at the end away from the current collector, so that a funnel-shaped pore channel can be formed in the thickness direction of the thick electrode sheet without residual multi-step holes, so as to improve the flow rate of the electrolyte in the thickness direction of the thick electrode sheet without residual multi-step holes, thereby solving the problem of difficult electrolyte infiltration; and the funnel-shaped pore channel helps to reduce the concentration polarization of the electrolyte in the thick electrode sheet without residual multi-step holes, so that the electrolyte can flow quickly into the inner layer of the coating; it also effectively reduces the problem that the coating at the end away from the current collector is easily deformed due to the large porosity resulting in greater force when the electrolyte infiltrates.

[0052] It can also be understood that if the pore sizes of adjacent coatings differ greatly, it is easy to cause a large pressure difference between adjacent coatings, resulting in deformation of some coatings. Therefore, in the present disclosure, the particle size difference of each adjacent ammonium bicarbonate solid particle is controlled to be 5um to 20um to ensure that the pressure difference between adjacent coatings is large and appropriate, thereby effectively avoiding the problem of deformation of the coatings when the electrolyte flows through adjacent coatings.

[0053] It should be noted that, by controlling the weight percentage of ammonium bicarbonate solid particles used to be: y = (0.1 ~ 0.4) * (n-1), the particle size of the ammonium bicarbonate solid particles is 20um ~ 60um, and the particle size of the ammonium bicarbonate solid particles gradually increases from the end close to the current collector to the end away from the current collector, and the particle size difference of each adjacent ammonium bicarbonate solid particle is 5um ~ 20um, so as to ensure that the prepared thick electrode sheet without residual multi-step pores forms a gradient gradient porous structure, and a funnel-shaped pore channel can be formed in the thickness direction, so that not only the concentration polarization of the electrolyte in the thick electrode sheet without residual multi-step pores is reduced, but also the lithium ion battery is reduced. Internal resistance, it also improves the circulation speed of the electrolyte, solves the problem of difficult electrolyte infiltration, avoids the problem that the thick electrode sheet without residual multi-step holes is prone to deformation at a higher circulation speed, and avoids the serious bulging around the holes caused by the large gas production during drying and gasification of the added ammonium bicarbonate solid particles due to their large particle size, thereby preparing a thick electrode sheet without residual multi-step holes with a smooth surface and low internal resistance, and ensures that the prepared thick electrode sheet without residual multi-step holes has a higher energy density, and ensures that the prepared thick electrode sheet without residual multi-step holes is not prone to structural collapse during multiple cycles, thereby improving the cycle performance of the lithium-ion battery.

[0054] It is understandable that, since the ammonium bicarbonate solid particles will generate a certain amount of gas when heated, it is generally necessary to add additional exhaust equipment to extract these gases to maintain the stability of the air pressure during drying, but this will cause the problem of high equipment cost. Therefore, in one embodiment, the temperature of the drying operation is 60°C to 100°C, and the time of the drying operation is 5min to 30min, so as to ensure that the ammonium bicarbonate solid particles can achieve a small and stable gas production during drying. In this way, the ammonium bicarbonate solid particles can be fully removed without adding additional exhaust equipment to ensure the formation of a gradient porous structure.

[0055] It can be understood that, due to the low decomposition temperature of the ammonium bicarbonate solid particles, when used, there is no need to adjust the traditional drying operation conditions, that is, the existing drying process can be used to achieve the effect of a small and stable gas production of the ammonium bicarbonate solid particles during drying. Specifically, in one embodiment, the drying operation is a multi-stage baking operation: baking at 70°C for 2min to 3min, baking at 80°C for 2min to 3min, baking at 90°C for 2min to 3min, and baking at 100°C for 2min to 3min in sequence to achieve a multi-stage baking operation of the coating, especially in conjunction with the weight percentage of the ammonium bicarbonate solid particles used in each coating operation is: y=(0.1~0.4)*(n-1) , wherein n is the number of coating operations, the particle size of the ammonium bicarbonate solid particles is 20um to 60um, and the particle size of the ammonium bicarbonate solid particles gradually increases from the end close to the current collector to the end away from the current collector, and the particle size difference of each adjacent ammonium bicarbonate solid particle is 5um to 20um, so as to ensure that the added ammonium bicarbonate solid particles can achieve continuous, stable and small amount of gas production in the multi-stage baking operation. In this way, on the one hand, the continuous and stable gas production can effectively avoid the problem of serious bulging around the hole caused by the ammonium bicarbonate solid particles generating a large amount of gas due to excessive heating, which is conducive to the smooth and crack-free surface of the prepared thick electrode sheet without residual multi-step holes; on the other hand, a small amount of gas production can be normally extracted by traditional baking equipment without the need to add additional vacuum equipment, thereby saving the use cost of the equipment.

[0056] In one of the embodiments, the rolling rate during the rolling operation is 80% to 90%.

[0057] It can be understood that since the self-decomposition products of ammonium bicarbonate solid particles are three different gases, the gaps between the active materials, the conductive agent and the adhesive in the coating after the drying process are larger than the gaps in the coating obtained by the traditional pore-forming agent using less than two gases, that is, the expansion degree of the coating disclosed in the present invention after drying is relatively high. If a rolling rate lower than 80% is used, a good rolling effect of the coating disclosed in the present invention cannot be achieved. If a rolling rate higher than 90% is used, it is easy to cause the active material particles to be crushed to affect the cycle performance of the lithium-ion battery. Therefore, in the present disclosure, the rolling rate is controlled to be 80% to 90% during the rolling operation of the present disclosure, so that a higher rolling rate can achieve a better rolling effect on the dried coating of the present disclosure, thereby effectively enhancing the close contact between the active material, the conductive agent and the adhesive, and effectively reducing the problem of bulging around the pores caused by the gasification of the ammonium bicarbonate solid particles, which leads to an increase in the internal resistance of the lithium-ion battery. The rolling operation also improves the smoothness and flatness of the coating surface of the thick electrode sheet without residual multi-step holes, which is conducive to the preparation of a thick electrode sheet without residual multi-step holes with a gradient gradient porous structure, small internal resistance, high liquid retention, and smooth and flat without cracks, thereby ensuring that the lithium-ion battery has high energy density, high cycle retention rate, low internal resistance and high liquid retention.

[0058] It can be understood that, since the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations, the expansion degree of each coating after drying will gradually increase from the end close to the current collector to the end away from the current collector, and in order to achieve a better rolling effect for each coating, it is usually adjusted according to the size of the expansion difference of each coating to increase its corresponding rolling rate. However, in actual applications, if the method of increasing the corresponding rolling rate is adjusted according to the size of the expansion difference of each coating, there is a problem that the pores of the first coating are easily crushed after subsequent multiple rolling. Therefore, in the present disclosure, by controlling the rolling rate of each rolling operation to be the same, the same rolling rate can better meet the expansion difference of each coating, so that the pores of the first coating are not easily crushed after subsequent multiple rolling, and then a funnel-shaped pore channel can be formed, which helps to reduce the concentration polarization of the electrolyte in the thick electrode sheet without residual multi-step pores, and improve the circulation rate of the electrolyte, solving the problem of difficult electrolyte infiltration.

[0059] In one of the embodiments, the solid content of the slurry is 40% to 75%, and the viscosity of the slurry is 5000 mPa.s to 7000 mPa.s.

[0060] It can be understood that for some slurries with relatively thin coating thickness, if the faster gas production rate causes bubbles to escape directly from the thinner slurry, the pores formed in the dried coating are uneven, which causes the subsequent electrolyte to enter the thick electrode sheet without residual multi-step holes due to uneven pores, causing the thick electrode sheet without residual multi-step holes to deform. Therefore, in the present disclosure, the viscosity of the slurry is controlled to be 5000mPa.s~7000mPa.s to ensure that the viscosity of the slurry is high, and the high-viscosity slurry has a large viscous resistance, which can effectively slow down the escape speed of bubbles, so that the bubbles can rise slowly in the slurry, so that more bubbles can gather in the slurry and form relatively dense bubbles, and the denser bubbles can discharge the liquid in the slurry and form channels perpendicular to the surface of the slurry, which helps to form uniform pores on the slurry, that is, the high-viscosity slurry helps to directional pore formation, thereby helping to form uniform pores, especially in conjunction with controlling the weight percentage of the ammonium bicarbonate solid particles used in each coating operation: y=(0.1~0.4)*(n-1) , when the particle size of the ammonium bicarbonate solid particles is 20um~60um and the particle size difference of each adjacent ammonium bicarbonate solid particles is 5um~20um, it can ensure that each layer of coating can form uniform pores, which helps the electrolyte to flow evenly on the thick electrode sheet without residual multi-step holes, and effectively avoid the problem of deformation of the electrolyte due to uneven force in the thick electrode sheet without residual multi-step holes.

[0061] It can also be understood that, since the solid content of the slurry is 40% to 75%, on the one hand, it ensures that the content of the liquid in the slurry is more compatible with the amount of ammonium bicarbonate solid particles added, so that the addition of a small amount of ammonium bicarbonate solid particles can achieve the effect of directional pore formation in the slurry, which is conducive to the preparation of uniform pores.

[0062] In the present disclosure, relatively thin slurry refers to a coating thickness of 25 um to 50 um in the coating operation.

[0063] In one embodiment, each coating operation of the n coating operations is a double-sided coating operation, that is, the first coating operation is a double-sided coating operation, the second coating operation is a double-sided coating operation, the third coating operation is a double-sided coating, and so on, so as to obtain a gradient porous structure on both sides of the thick aluminum foil.

[0064] It can be understood that, since the gradient difference porous structures are formed on both sides of the thick aluminum foil, the two gradient difference porous structures can be symmetrically centered with the thick aluminum foil. Compared with the single-sided gradient difference porous structure, the two symmetrical gradient difference porous structures can better reduce the polarization difference of the thick electrode sheet, better reduce the internal resistance of the thick electrode sheet, and improve the cycle performance of the lithium-ion battery. Further, the double-sided coating disclosed in the present invention refers to simultaneous coating, for example, the slurry of the coating operation is coated on both sides of the thick aluminum foil using a double coating wheel, followed by a drying operation and a rolling operation, and then a second double-sided coating is performed, followed by a drying operation and a rolling operation, and so on, until n double-sided coating operations are completed.

[0065] In one embodiment, the slurry is a positive electrode slurry, and the active material of the positive electrode slurry includes the following weight percentages: 96.0% to 99.0% positive electrode material, 0.5% to 1.5% conductive agent and 0.5% to 2.0% binder, so as to ensure the preparation of a high energy density thick electrode sheet without residual multi-step holes, thereby ensuring the preparation of a high energy density lithium-ion battery.

[0066] In one embodiment, the positive electrode material includes LiCoO2, LiMn2O4, LiFePO4 and Li(Ni x Co y Mn z ) at least one of O2.

[0067] In one embodiment, the conductive agent includes at least one of SP (carbon black conductive agent) and CNT (carbon nanotube).

[0068] In one embodiment, the binder includes at least one of polyvinylidene fluoride and sodium carboxymethyl cellulose.

[0069] In a preferred embodiment, n is 3.

[0070] The present disclosure also provides a thick electrode sheet with no residual multi-step holes, which is prepared by the preparation method of the thick electrode sheet with no residual multi-step holes described in any of the above embodiments. It can be understood that since the preparation method of the thick electrode sheet with no residual multi-step holes disclosed in the present disclosure makes full use of the low-temperature easy decomposition and no residue characteristics of the solid particles of ammonium bicarbonate, it ensures that the coating is not easy to crack during the drying process, and there is no need to add additional exhaust equipment and adjust the drying conditions, which saves the adjustment workload of drying and reduces the use cost of the equipment. In this way, under the premise of ensuring that a thick electrode sheet with no residual multi-step holes with high energy density is prepared, the problem of the electrolyte being difficult to infiltrate the thick electrode sheet with no residual multi-step holes is solved, the electrolyte retention amount of the thick electrode sheet with no residual multi-step holes is increased, and the internal resistance of the thick electrode sheet with no residual multi-step holes is reduced, thereby improving the cycle performance of the lithium-ion battery.

[0071] The present disclosure also discloses a lithium-ion battery, comprising a thick electrode sheet without residual multi-step holes as described in any of the above embodiments. It can be understood that the thick electrode sheet without residual multi-step holes prepared by the method for preparing the thick electrode sheet without residual multi-step holes is applied to the lithium-ion battery, because the thick electrode sheet without residual multi-step holes has the characteristics of a porous structure with a gradient gradient, a small internal resistance, a high liquid retention capacity, and a smooth and flat surface without cracks, thereby effectively improving the cycle performance of the lithium-ion battery.

[0072] Compared with the prior art, the present invention has at least the following advantages:

[0073] 1) Since the added ammonium bicarbonate solid particles will decompose to form ammonia, water vapor and carbon dioxide gas when heated during drying, the gas generated by the decomposition helps to form a porous structure, and the generated ammonia, water vapor and carbon dioxide gas will be pumped away, effectively avoiding the problem of residual impurities in thick electrode sheets, so as to ensure that the added ammonium bicarbonate solid particles will not have residual impurities. In this way, it is ensured that the prepared electrode sheet has a structure without residual multi-step pores, thereby effectively avoiding the problem of traditional residual impurities affecting the internal resistance of lithium-ion batteries.

[0074] 2) Since the decomposition temperature of ammonium bicarbonate solid particles is between 30°C and 60°C, the drying temperature of the present invention is significantly lower than that of traditional iodine, aluminum chloride, and sodium bicarbonate. This effectively avoids the occurrence of undesirable phenomena such as cracking of thick electrode sheets during the drying process, while also saving energy consumption for drying and effectively reducing the preparation cost.

[0075] 3) Since the slurry of the first coating operation does not contain ammonium bicarbonate solid particles; the slurries of the second coating operation to the nth coating operation all contain ammonium bicarbonate solid particles, and the amount of the ammonium bicarbonate solid particles used in each coating operation increases with the increase in the number of coating operations; at the same time, in conjunction with the drying and rolling operations, the gradient gradient porous structure of the thick electrode sheet is finally prepared, that is, the porosity of the coating close to the current collector is smaller than the porosity of the coating far from the current collector. In this way, the gradient gradient porous structure is conducive to the rapid penetration of the electrolyte to accelerate the movement of lithium ions in the thick electrode sheet, effectively avoiding the problem of increased internal resistance due to the electrolyte not penetrating the thick electrode sheet, and the gradient gradient porous structure helps to increase the electrolyte retention amount, thereby improving the cycle retention rate of the lithium-ion battery.

[0076] 4) Since the slurry is dried and rolled in sequence after each coating operation, each coating operation needs to be dried and rolled, thereby realizing multiple batch drying and multiple batch rolling operations of the current collector and the coating, so as to prepare a thick electrode sheet with a gradient gradient porous structure with increasing porosity and a smooth and flat coating without cracks, effectively avoiding the problem of particle breakage and pulverization of the active material caused by uneven or excessive rolling pressure in traditional single rolling.

[0077] Compared with the prior art, the present invention has at least the following advantages:

[0078] Some specific examples are given below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.

[0079] Embodiment 1:

[0080] (1) Preparation of the first positive electrode slurry: LiNi 0.5 Co 0.2 Mn 0.3 The weight percentage of O2, SP, and PVDF used is LiNi 0.5 Co 0.2 Mn 0.3 O2:SP:PVDF=97.4%:1.2%:1.4%; LiNi 0.5 Co 0.2 Mn 0.3 O2 was added to PVDF and stirred evenly, and then SP was added and stirred evenly. The prepared positive electrode slurry had a viscosity of 7000 mPa.s and a solid content of 70%;

[0081] (2) coating the positive electrode slurry of step (1) on one side of a 13 μm aluminum foil, and the coating thickness on one side is 25 μm, to obtain a thick electrode sheet A without residual multi-step holes;

[0082] (3) subjecting the thick electrode sheet A without residual multi-step holes to a multi-stage baking operation in sequence, baking at 70° C. for 3 min, baking at 80° C. for 2 min, baking at 90° C. for 2 min, and baking at 100° C. for 3 min, to obtain a thick electrode sheet B without residual multi-step holes;

[0083] (4) The dried thick electrode sheet B without residual multi-step pores is pre-rolled for the first time, and the rolling rate is 80%;

[0084] (5) Preparation of the second positive electrode slurry: LiNi 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2:SP:PVDF:ammonium bicarbonate solid particles = 97.2%:1.2%:1.4%:0.2%, LiNi 0.5 Co 0.2 Mn 0.3 O2 was added to PVDF and stirred evenly, and then SP and ammonium bicarbonate solid particles were added and stirred evenly. The prepared positive electrode slurry had a viscosity of 7000 mPa.s and a solid content of 70%. The particle size of the ammonium bicarbonate solid particles was 20 um (Sinopharm Chemical Reagent Co., Ltd.).

[0085] (6) coating the positive electrode slurry of step (4) on one side of the thick electrode sheet B without residual multi-step holes, and the coating thickness on one side is 30 μm, to obtain a thick electrode sheet C without residual multi-step holes;

[0086] (7) subjecting the thick electrode sheet C without residual multi-step holes to a multi-stage baking operation in sequence, baking at 70° C. for 3 min, baking at 80° C. for 2 min, baking at 90° C. for 2 min, and baking at 100° C. for 3 min, to obtain a thick electrode sheet D without residual multi-step holes;

[0087] (8) The dried thick electrode sheet D without residual multi-step pores is rolled for the second time, and the rolling rate is 80%;

[0088] (9) Preparation of the third positive electrode slurry: LiNi 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2: SP: PVDF: ammonium bicarbonate solid particles = 97.1%: 1.2%: 1.4%: 0.3%, LiNi0.5 Co 0.2 Mn 0.3 O2 was added to PVDF and stirred evenly, and then SP and ammonium bicarbonate solid particles were added and stirred evenly. The prepared positive electrode slurry had a viscosity of 7000 mPa.s and a solid content of 70%. The particle size of the ammonium bicarbonate solid particles was 30 um (Sinopharm Chemical Reagent Co., Ltd.).

[0089] (10) coating the positive electrode slurry of step (8) on one side of the thick electrode sheet D without residual multi-step holes, and the coating thickness on one side is 30 μm, to obtain a thick electrode sheet E without residual multi-step holes;

[0090] (11) subjecting the thick electrode sheet E without residual multi-step holes to a multi-stage baking operation in sequence, baking at 70° C. for 3 min, baking at 80° C. for 2 min, baking at 90° C. for 2 min, and baking at 100° C. for 3 min, to obtain a thick electrode sheet F without residual multi-step holes;

[0091] (12) The dried thick electrode sheet F without residual multi-step pores is rolled for the third time, with a rolling rate of 80%, to obtain a thick electrode sheet without residual multi-step pores.

[0092] Embodiment 2:

[0093] The difference from Example 1 is that the preparation of the second positive electrode slurry in step (5) of Example 2 and the formulation of the third positive electrode slurry in step (9) are different, that is, the LiNi in step (5) of Example 2 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2: SP: PVDF: ammonium bicarbonate solid particles = 97.0%: 1.2%: 1.4%: 0.4%, the viscosity of the prepared positive electrode slurry is 7000mPa.s, the solid content is 70%, and the particle size of the ammonium bicarbonate solid particles is 30um (Sinopharm Chemical Reagent Co., Ltd.);

[0094] (9) Preparation of the third positive electrode slurry: LiNi 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3O2: SP: PVDF: ammonium bicarbonate solid particles = 96.6%: 1.2%: 1.4%: 0.8%, the viscosity of the prepared positive electrode slurry is 7000mPa.s, the solid content is 70%, and the particle size of the ammonium bicarbonate solid particles is 50um (Xilong Chemical);

[0095] Embodiment 3:

[0096] The difference from Example 1 is that the preparation of the second positive electrode slurry in step (5) of Example 3 and the formulation of the third positive electrode slurry in step (9) are different, that is, the LiNi in step (5) of Example 3 is 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2: SP: PVDF: ammonium bicarbonate solid particles = 97.1%: 1.2%: 1.4%: 0.3%, the viscosity of the prepared positive electrode slurry is 7000mPa.s, the solid content is 70%, and the particle size of the ammonium bicarbonate solid particles is 55um (Xilong Chemical);

[0097] (9) Preparation of the third positive electrode slurry: LiNi 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2: SP: PVDF: ammonium bicarbonate solid particles = 96.8%: 1.2%: 1.4%: 0.6%, the viscosity of the prepared positive electrode slurry is 7000mPa.s, the solid content is 70%, and the particle size of the ammonium bicarbonate solid particles is 60um (Xilong Chemical).

[0098] Comparative Example 1

[0099] The difference from Example 2 is that the preparation of the second positive electrode slurry in step (5) of Comparative Example 1 and the formulation of the third positive electrode slurry in step (9) are different, that is, the LiNi 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2: SP: PVDF: ammonium bicarbonate solid particles = 97.35%: 1.2%: 1.4%: 0.05%, step (9) preparation of the third positive electrode slurry: LiNi0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2:SP:PVDF:ammonium bicarbonate solid particles = 96.9%:1.2%:1.4%:0.5%, and the rest remain unchanged.

[0100] Comparative Example 2

[0101] The difference from Example 2 is that the particle size of the ammonium bicarbonate solid particles in step (5) of Comparative Example 2 and the particle size of the ammonium bicarbonate solid particles in step (9) are different, that is, the particle size of the ammonium bicarbonate solid particles in step (5) of Comparative Example 2 is 80 μm; the particle size of the ammonium bicarbonate solid particles in step (9) is 100 μm, and the rest remain unchanged.

[0102] Comparative Example 3

[0103] The difference from Example 2 is that the particle size of the ammonium bicarbonate solid particles in step (5) of Comparative Example 3 and the particle size of the ammonium bicarbonate solid particles in step (9) are different, that is, the particle size of the ammonium bicarbonate solid particles in step (5) of Comparative Example 2 is 10 um; the particle size of the ammonium bicarbonate solid particles in step (9) is 12 um, and the rest remain unchanged.

[0104] Comparative Example 4

[0105] The difference from Example 2 is that the rolling rate in steps (4), (8) and (12) of Example 4 is 75%, and the rest remains unchanged.

[0106] Comparative Example 5

[0107] The difference from Example 2 is that the rolling rate in steps (4), (8) and (12) of Example 5 is 95%, and the rest remains unchanged.

[0108] Comparative Example 6

[0109] The difference from Example 2 is that the rolling rate of step (4) of comparative example 6 is 75%, the rolling rate of step (12) is 90%, and the rest remains unchanged.

[0110] Comparative Example 7

[0111] The difference from Example 2 is that the preparation formula of the second positive electrode slurry in step (5) of Comparative Example 7 is different, that is, in step (5) of Comparative Example 7, LiNi 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi0.5 Co 0.2 Mn 0.3 O2:SP:PVDF:ammonium bicarbonate solid particles = 97.3%:1.2%:1.1%:0.4%. The viscosity of the prepared positive electrode slurry is 4800mPa.s, the solid content is 50%, and the rest remains unchanged.

[0112] Comparative Example 8

[0113] The difference from Example 2 is that the preparation formula of the second positive electrode slurry in step (5) of Comparative Example 8 is different, that is, in step (5) of Comparative Example 8, LiNi 0.5 Co 0.2 Mn 0.3 Weight percentage of O2, SP, PVDF and ammonium bicarbonate solid particles: LiNi 0.5 Co 0.2 Mn 0.3 O2:SP:PVDF:ammonium bicarbonate solid particles = 96.4%:1.2%:2%:0.4%, so that the viscosity of the prepared positive electrode slurry is 10000mPa.s, the solid content is 75%, and the rest remains unchanged.

[0114] Comparative Example 9

[0115] The difference from Example 2 is that: Comparative Example 8 changes one side of step (2), step (6) and step (10) in Example 2 to double sides, that is, each coating operation of n coating operations is a double-sided coating operation.

[0116] The thick electrode sheets without residual multi-step pores prepared in the above Examples 1 to 3 and Comparative Examples 1 to 9, the negative electrode sheets and the separators were made into lithium ion batteries, and then the lithium ion batteries were tested for liquid retention, resistance and 300 cycle retention rate, and the appearance of the thick electrode sheets without residual multi-step pores was also tested to obtain the following table data:

[0117]

[0118] From the comparison between Examples 1 to 3 and Comparative Example 1, it can be seen that when the weight percentage of the ammonium bicarbonate solid particles of Examples 1 to 3 is: y=(0.1-0.4)*(n-1), the ammonium bicarbonate solid particles of Examples 1 to 3 are more suitable, which is helpful to form the porosity of the porous structure with a gradient difference, so that the comprehensive indicators of Examples 1 to 3 are significantly better than those of Comparative Example 1, among which the comprehensive indicators of Example 2 are better.

[0119] From the comparison between Example 2 and Comparative Examples 2 to 3, it can be seen that since the particle size of the ammonium bicarbonate solid particles of Example 2 is 20um to 60um, and the particle size of the ammonium bicarbonate solid particles gradually increases from one end close to the current collector to the end away from the current collector, the particle size difference between each adjacent ammonium bicarbonate solid particle is 5um to 20um, so that the comprehensive index of Example 2 is significantly better than that of Comparative Examples 2 to 3.

[0120] From the comparison between Example 2 and Comparative Examples 4 to 6, it can be seen that since the rolling rates in steps (4), (8) and (12) of Example 2 are between 80% and 90%, and the rolling rates of each rolling operation in steps (4), (8) and (12) of Example 2 are the same, the pores of the first coating are not easily crushed after subsequent multiple rolling operations, which helps to form funnel-shaped pore channels, making the comprehensive indicators of Example 2 significantly better than those of Comparative Examples 4 to 6.

[0121] From the comparison between Example 2 and Comparative Examples 7 to 8, it can be seen that since the second positive electrode slurry in step (5) of Example 2 is at 5000mPa.s to 7000mPa.s and the solid content is 40% to 75%, it is helpful for the ammonium bicarbonate solid particles to form pores in a directional manner, thereby helping to form uniform pores, so that the comprehensive indicators of Example 2 are significantly better than those of Comparative Examples 7 to 8.

[0122] From the comparison between Example 2 and Comparative Example 9, it can be seen that since each of the n coating operations in Comparative Example 9 is a double-sided coating operation, under the same unit volume, the two symmetrical gradient gradient porous structures of Comparative Example 9 can better reduce the polarization difference of the thick electrode sheet, better reduce the internal resistance of the thick electrode sheet, and improve the cycle performance of the lithium-ion battery, so that the comprehensive indicators of Comparative Example 9 are significantly better than those of Example 2.

[0123] The above-mentioned embodiments only express several implementation methods of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the disclosed patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present disclosure, and these all belong to the protection scope of the present disclosure. Therefore, the protection scope of the disclosed patent shall be subject to the attached claims.

Claims

1. A method for preparing a thick electrode sheet without residual multi-step holes, comprising: obtaining a current collector; The slurry is coated n times in sequence, where n is greater than or equal to 3 and n is a positive integer; It is characterized in that The slurry of the first coating operation does not contain solid ammonium bicarbonate particles; the slurries of the second coating operation to the nth coating operation all contain the solid ammonium bicarbonate particles, and the amount of the solid ammonium bicarbonate particles used in each coating operation increases with the increase in the number of coating operations; The preparation method further comprises: The slurry is dried and rolled in sequence after each coating operation, so that the ammonium bicarbonate solid particles are gasified during drying, so that the obtained thick electrode sheet without residual multi-step pores can form a gradient-differential porous structure, and the porosity of the gradient-differential porous structure gradually increases from one end close to the current collector to the end away from the current collector.

2. The method for preparing a thick electrode sheet without residual multi-step holes according to claim 1, characterized in that: The weight percentage of the ammonium bicarbonate solid particles used in each coating operation is: y=(0.1~0.4)*(n-1) , where n is the number of coating operations.

3. The method for preparing a thick electrode sheet without residual multi-step holes according to claim 1, characterized in that: The temperature of the drying operation is 60° C. to 100° C., and the time of the drying operation is 5 min to 30 min.

4. The method for preparing a thick electrode sheet without residual multi-step holes according to claim 1, characterized in that: The rolling rate during the rolling operation is 80% to 90%.

5. The method for preparing a thick electrode sheet without residual multi-step holes according to claim 1, characterized in that: The solid content of the slurry is 40% to 75%, and the viscosity of the slurry is 5000 mPa.s to 7000 mPa.s.

6. The method for preparing a thick electrode sheet without residual multi-step holes according to claim 1, characterized in that: The slurry is a positive electrode slurry, and the active material of the positive electrode slurry includes the following weight percentages: 96.0% to 99.0% positive electrode material, 0.5% to 1.5% conductive agent and 0.5% to 2.0% binder.

7. The method for preparing a thick electrode sheet without residual multi-step holes according to claim 6, characterized in that: The positive electrode materials include LiCoO2, LiMn2O4, LiFePO4 and Li(Ni x Co y Mn z ) at least one of O2.

8. The method for preparing a thick electrode sheet without residual multi-step holes according to claim 1, characterized in that: The coating thickness of the coating operation is 25um to 50um; and / or, Each coating operation of the n coating operations is a double-sided coating operation.

9. A thick electrode sheet without residual multi-step holes, characterized in that: The thick electrode sheet without residual multi-step holes is prepared by the method for preparing the thick electrode sheet without residual multi-step holes according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: A thick electrode sheet without residual multi-step holes as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of porous pole piece of sodium ion battery

    CN114914392A

  • Electrode plate preparation method, electrode plate and battery

    CN115548273A

  • Ammonium bicarbonate pore-forming agent and process for preparing membrane electrode

    CN1259744C

Cited By

  • Positive plate with gradient pores, preparation method of positive plate, lithium ion battery and electric device

    CN121260735A